A Qualitative Analysis of Team-Sport Referee Experience - Jason Milne (Journal of Public and Professional Sociology)
The sport referee is an integral part of the sporting experience. This paper explores the experience of the sport official, focusing on developing themes related to how an individual got into the refereeing, current issues sport officials experience both on and off the field, and relationships between the official and other sporting roles. Through interviews (N=10) with referees from a variety of team sports, I use the grounded theory (Strauss and Corbin 1990) method to develop a series of themes that emerged from the data focusing on the sport referee experience. I developed initial themes that focus on the different questions from the surveys. Out of these initial themes, I used theoretical coding to develop theories that focus on the referee role that is in conflict with other sporting roles as well as the referee identity in and of itself, the importance of social and cultural capital for improvement and advancement of the referee, and the role of safety and fairness for the sport official. Future research should focus on the application of these ideas for the improvement of referee organizations, particularly increasing the number of referees who have an opportunity to advance. Future research should also focus on examining the refereeing system from other role-perspectives, focusing particularly on the difference between those involved in the actual game (players, coaches, and spectators), and those involved in the administration of the game (league administrators, etc.).